Acute gastric volvulus six years after PEG-tube placement - Jonathan Hencke; Gabriel Nonnenmacher; Steffan Loff (Journal of Pediatric Surgery Case Reports, 2022)
Gastric volvulus (GV) is a rare condition in children, occurring either acute or chronically, usually requiring surgical treatment. It results from increased gastric mobility due to absent or attenuated gastric ligaments. Known associations exist with diaphragmatic eventration, diaphragmatic hernia, hiatal hernia and asplenia. Cases of GV following gastrostomy are extremely rare; we report the 6th case world-wide. Our patient, an eleven year old girl with cerebral palsy, presented with a fulminant GV and pneumoperitoneum. She underwent emergency laparotomy revealing gastric necrosis and a large perforation. After closing the defect, we performed a scheduled relaparotomy four days later, and resected the remaining clearly marked necrosis, leaving a considerably smaller stomach, but preventing a gastrectomy. With this report, we would like to draw attention to this life-threatening condition and possible complication of gastrostomies.